Penyelenggaraan Mal Pelayanan Publik di Kabupaten Batang Perspektif Maqashid Syariah - Kana Akhsinawati; Ahmad Fauzan (Department of Constitutional Law, Faculty of Sharia, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This research is related to the implementation of Public Service Malls in Batang Regency Maqashid Syariah Perspective regarding the suitability of implementing Public Service Malls based on Presidential Regulation Number 89 of 2021, this regulation is the new legal basis for the implementation of Public Service Malls which was previously regulated in PERMENPAN-RN Number 23 of 2017. The changes to these regulations have resulted in a delay in the conformity that must be implemented at the Public Service Mall in Batang Regency. From this background, there are two problem formulations, namely 1). Is the implementation of MPP in accordance with Presidential Regulation No. 89 of 2021?., 2). How is Maqāṣid asy-Syarīʻah's review of the implementation of the Public Service Mall in Batang district? This research is a qualitative field research with an Empirical Juridical and Islamic Maqasid approach. The results of this study regarding the implementation of Public Service Malls in Batang Regency 1) there is no regional head regulation that regulates its implementation, the principles have not been realized such as being efficient because the website management has not been able to meet/cover all the information needs of the community, the principle of accountability has not been fulfilled, not yet there is an internal evaluation of MPP and accountability reports to measure overall performance, limited services present at MPP and some of these service methods do not meet the principles of accessibility, the unavailability of independent services and mobile services as a service model in MPP where this is not in accordance with the provisions stipulated in Presidential Regulation Number 89 of 2021., 2). The implementation of Public Service Malls in Batang Regency in terms of Maqashid Syariah Jasser Auda is very relevant in improving services for the public interest. And in its implementation it requires interrelated systems to help realize the goals (benefit) to be achieved.